2011
DOI: 10.1002/elan.201100137
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid‐Based, Liquid‐Junction‐Free Reference Electrode

Abstract: In this paper, we describe a new type of polymer membrane-based reference electrode (RE) based on ionic liquids (ILs), in both liquid-contact (LCRE) and solid-contact reference electrode (SCRE) forms. The ILs used were bis(-trifluoromethane sulfonyl)amid with 1-alkyl-3-methyl-imidazolium as well as phosphonium and ammonium cations. In addition to their charge stabilisation role, it was found that the ILs also functioned as effective plasticizers in the PVC matrix. The LCREs and SCREs were prepared using the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 20 publications
(19 reference statements)
3
58
0
Order By: Relevance
“…Each reference electrode was filled with an internal solution of [C 2 mim][Cl] in the corresponding RTIL and all of them were stored five days before use [28]. The stability of their electrode potential values through time was determined by cyclic voltammetry (CV) of the cobaltocenium ion, [Co(Cp) 2 ] + , at gold electrodes, since the cobaltocenium/cobaltocene redox couple, [Co(Cp) 2 ] +/0 , is a reliable internal standard for calibration of the RE potential in different nonaqueous media, as well as in RTILs [15,29] 2 ] +/0 couple.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Each reference electrode was filled with an internal solution of [C 2 mim][Cl] in the corresponding RTIL and all of them were stored five days before use [28]. The stability of their electrode potential values through time was determined by cyclic voltammetry (CV) of the cobaltocenium ion, [Co(Cp) 2 ] + , at gold electrodes, since the cobaltocenium/cobaltocene redox couple, [Co(Cp) 2 ] +/0 , is a reliable internal standard for calibration of the RE potential in different nonaqueous media, as well as in RTILs [15,29] 2 ] +/0 couple.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The reference membranes are usually doped with ions that can leach into the samples on a slow but continuous basis so that the phase boundary potentials at the reference membrane/sample interfaces are sample-independent and defined by the interfacial distribution of the doping ions. Several ions have been doped into reference membranes, including polyions, 18 ionic liquids, [19][20][21] lipophilic and hydrophilic salts. [22][23][24] At the reference membrane/solid contact interface, the interfacial potential can be stabilized by employing various solid contacts that are also used in all-solid-state ISEs.…”
Section: Introductionmentioning
confidence: 99%
“…As novel designs for reference electrodes that, for example, do not rely on an inner-filling solution, are much needed, IL related developments emerging from materials science research may offer advantages. For instance, Cicmil et al (115,116) reported on the use of ILs in polyvinyl chloride (PVC) matrices for the preparation of disposable reference electrodes in which the partitioning of the ions into the liquid phase defines the interfacial potential. After comparing several ILs, the authors found that reference electrodes prepared with 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl) imide [C 2 mim][NTf 2 ] were least sensitive to changes in the concentration of common alkali metal chlorides.…”
Section: Ionic Liquids In Biosensorsmentioning
confidence: 99%